Carbon dot-doped sodium borosilicate gel glasses with emission tunability and their application in white light emitting diodes. Issue 26 (8th June 2015) - Ma, Li; Xiang, Weidong; Gao, Haihong; Pei, Lang; Ma, Xin; Huang, Yunyun; Liang, Xiaojuan
Abstract : Carbon dot (CD)-doped sodium borosilicate gel (CD-NBS gel) glasses were successfully prepared by incorporating the CDs into sodium borosilicate networks. Abstract : Carbon dot (CD)-doped sodium borosilicate gel (CD-NBS gel) glasses were successfully prepared by incorporating the CDs into sodium borosilicate networks. The structural and luminescence properties of highly flexible CD-NBS gel glasses with 5% wt% to 70 wt% CDs were studied. Images of the CD-NBS gel glasses captured using a transmission electron microscope demonstrated the uniformity and good dispersibility of the glasses. Red-shifted emission and enhanced quantum efficiency were observed when the doping concentration of CDs in the NBS gel glasses increased. The enhanced fluorescence properties of the CD-NBS gel glasses were considered to originate from the surface modification of CDs with high dopant concentration in the gel glasses. CD-based white light-emitting diodes (W-LEDs) were developed by combining the yellow light-emitting CD-NBS gel glasses with blue GaN-based LED chips. The as-fabricated W-LEDs exhibited the optimised colour coordinates of (0.32, 0.33), the colour rendering index up to 78.9, and the maximum luminous efficacy exceeding 58.1 lm W −1 by the use of the CD-NBS gel glasses at different concentrations of CDs. These results indicate that this new kind of CD-NBS gel glass would be a promising candidate for W-LEDs.